Criminals as Animals from Shakespeare to Lombroso. - Olson, Greta (Law & Literature., 2013)
Criminals as Animals demonstrates how animal metaphors have been used to denigrate persons identified as criminal in literature, law, and science. It traces the popularization of the 'criminal beast' metaphor in the late 16th century, the troubling of the trope during the long 18th century, and the later discovery of criminal atavism. It concludes that criminal-animal metaphors influence punitive treatments of prisoners and the poor even today.